Phenolic Acid Rich Fraction Of Gynura Procumbens As Potential Antihyperlipidemic And Antioxidant Agents - Murugesu, Kisantini (2018)
G. procumbens is found in most of the Southeast Asian countries and the leaves are used as a folk medicine to treat various illnesses including hyperlipidemia. The objectives of the present study include isolation of marker compound(s), standardization and phytochemical analysis of G. procumbens plant samples and investigation of their antioxidant and antihyperlipidemic effects in acute and chronic rat models, determination of their mechanisms of action and toxicological profiles. The leaves of G.procumbens were macerated with 95 % ethanol and fractionated into three fractions.